Determination of 17 β-estradiol in pharmaceutical preparation by UV spectrophotometry and high performance liquid chromatography methods - Bilal Yilmaz; Yucel Kadioglu (Arabian Journal of Chemistry, 2017)
In this study, new, rapid UV spectrophotometry (UV) and reversed phase high performance liquid chromatography (HPLC) methods were developed for the determination of 17 β-estradiol in pure and in pharmaceutical dosage form. The solvent system, wavelength of detection and chromatographic conditions were optimized in order to maximize the sensitivity of both the proposed methods. The linear regression equations obtained by least square regression method were y = 0.0184x + 0.0059 for the UV method and y = 56742x − 3403.6 for the HPLC method. The developed methods were successfully employed with a high degree of precision and accuracy for the estimation of total drug content in a commercial tablet of 17 β-estradiol. The results obtained from the UV method were compared with those obtained by using HPLC. The proposed methods are highly sensitive, precise and accurate and can be used for the reliable quantitation of 17 β-estradiol in pharmaceutical dosage form.